Towards an integrated control system for a scrap-free circular production of lithium-ion batteries - Naumann, Aleksandra; Süß, Sandro; Mennenga, Mark; Herrmann, Christoph (Procedia CIRP, 2023)
Battery production is an energy-intensive process with scrap rates between 5 % and 30 %. Therefore, concepts such as in-production recycling and Circulation Factories can improve energy and resource efficiency by connecting production and recycling operations. The secondary material, or more specifically the post-production material from recycling is a new variable in the production system and its amount varies according to the scrap rate. To handle resulting process interrelations and overall equipment efficiency in production and recycling, data from both has to be merged and considered coherently. Additionally, final product quality is affected by material degradation effects due to multiple feeding of already recycled post-production material. Based on cyber-physical control systems with elements such as virtual quality gates, an architecture for an operations control system in the circular production is proposed and transferred to the production of battery cells. This system should be able to consider different production goals such as product quality as well as material and energy efficiency. Therefore, the developed architecture reveals process interrelations using data mining and proposes adjustments to the set of control variables. Finally, different approaches are investigated and a “simple-to-complex-roadmap” for the practical implementation of operations control systems in circular production is derived.